Implementation Of Prims Algorithm In Primary Electrical Distribution Network - kustanto kustanto (Jurnal Ilmiah SINUS, 2010)
Optimization problem is the demanding problem for optimum solutions. The optimum (best) solution is a solution with minimum values, or maximum among a set of possible alternative solutions. In electrical distribution network, problem of demanding achievement of optimum condition of system operational performance is essential. One of the factors necessary to consider in the designing of the primary electrical distribution network is cost. Cost is closely related to length of cable used. It highlights the importance of calculating the minimum length of cable required in a network. The cable should be not only with as minimal as possible in length, but also regulated for better arrangement.Actually, in regulating the cable installation, longer path is more frequently selected. One of the ways of achieving optimization condition is to use algorithm to determine a minimum spanning tree of the primary electrical distribution network system. In this study, the algorithm used is Prims algorithman algorithm in graph theory to seek a minimum spanning tree for a weighted connected graph. In other word, it is a set of parts from branches of a tree consisting of all vertices, where the entire weight of all the branches of tree is the lowest.The study was conducted by designing a graph model of primary electrical distribution network in appropriate with the data obtained. Based on the graph, each was weighted for distance or length of network cable by using the ArcView GIS 3.3 and Delphi 7. The data were then calculated and simulated by using computer to gain a minimum spanning tree of the primary electrical distribution network using the Prims algorithm. Finally, time complexity in implementation of Prims algorithm in the primary electrical distribution network was studied in relation to efficiency of the algorithm.Keywords: Minimum Spanning Tree, Prims Algorithm, Time Complexity